Relevance and Definition of Consumer Behavior for the Successful Marketing - Arshi Naim (European Science Publishing, 2023)
Consumer behavior is the study of consumers and the processes they use to choose, use (consume), and dispose of products and services, including consumers’ emotional, mental, and behavioral responses. Consumer behavior incorporates ideas from several sciences including psychology, biology, chemistry, and economics. Studying consumer behavior is important because it helps marketers understand what influences consumers’ buying decisions. By understanding how consumers decide on a product, they can fill in the gap in the market and identify the products that are needed and the products that are obsolete. Studying consumer behavior also helps marketers decide how to present their products in a way that generates a maximum impact on consumers. Understanding consumer buying behavior is the key secret to reaching and engaging the clients, and converting them to purchase from the firm.
Keywords: Consumer Behavior; Consumers’ Buying Decisions; Market